ChemInform Abstract: A Voyage into the Synthesis and Photophysics of Homo‐ and Heterobinuclear Ensembles of Phthalocyanines and Porphyrins. Issue 50 (10th December 2013) - de la Torre, Gema; Bottari, Giovanni; Sekita, Michael; Hausmann, Anita; Guldi, Dirk M.; Torres, Tomas
Abstract Review: 281 refs.